Pembelajaran Berdiferensiasi untuk Meningkatkan Pemecahan Masalah Matematika: Penelitian Tindakan Kelas di Sekolah Dasar - Fadilatul Khoiriyah; Via Yustitia; Wiwik Supratiwi (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to improve the problem-solving abilities of second-grade students at SD Negeri Dukuh Menanggal 1 Surabaya in mathematics through the application of differentiated learning in fraction material. This Classroom Action Research (CAR) was conducted in two cycles. In the first cycle, the test results showed that the average student score was 68.82, with a learning mastery rate of 37.5%. Only 9 out of 24 students passed, while 15 others had not yet met the minimum passing criteria. This was due to the use of conventional teaching methods and the teacher's lack of understanding of differentiated learning. After improvements were made in the second cycle, the students' average score increased to 81.17, with a learning mastery rate of 96% (23 students passed). The results of this study indicate that differentiated learning can significantly improve students' problem-solving abilities in fraction material and make learning more meaningful and interactive.